2017
DOI: 10.17157/mat.4.3.462
|View full text |Cite
|
Sign up to set email alerts
|

‘They overworked us’

Abstract: In this article, I describe the institutional humiliation experienced by volunteer nurses in Sierra Leone following the end of the Ebola epidemic. They had been promised formal employment with the Ministry of Health and Sanitation after working in the Ebola treatment units in the country, but were dismissed from the hospitals where they were volunteering and felt humiliated. I suggest that this maltreatment of volunteer nurses cannot be grasped through the existing categories and parameters used by global heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…However, most reported that they have been disappointed as this promise did not materialise. In a study in Sierra Leone, volunteer nurses were similarly promised jobs during the Ebola crises only to be later denied by the government 11 . In this study, some volunteers even go to the length of asking for improved pay from the Officer‐in‐Charge, highlighting prevailing socioeconomic challenges and the hardships encountered in managing the stipends promised to them.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…However, most reported that they have been disappointed as this promise did not materialise. In a study in Sierra Leone, volunteer nurses were similarly promised jobs during the Ebola crises only to be later denied by the government 11 . In this study, some volunteers even go to the length of asking for improved pay from the Officer‐in‐Charge, highlighting prevailing socioeconomic challenges and the hardships encountered in managing the stipends promised to them.…”
Section: Discussionmentioning
confidence: 84%
“…In a study in Sierra Leone, volunteer nurses were similarly promised jobs during the Ebola crises only to be later denied by the government. 11 In this study, some volunteers even go to the length of asking for improved pay from the Officer-in-Charge, highlighting prevailing socioeconomic challenges and the hardships encountered in managing the stipends promised to them. As demonstrated in another study, acceding to this request may offer hope, further boosting the commitment of volunteers.…”
Section: To Quit or Not Quitmentioning
confidence: 96%
See 1 more Smart Citation
“…Any critique of the biomedical response has to reckon with this tragedy, and I certainly do not blame healthcare professionals-some of whom I count as friends-who risked their lives in efforts to quell the Ebola epidemic. These workers faced stigma and rejection from their communities, and many did not receive the remuneration their work deserved (Park 2017). Moreover, rates of hospital transmission dropped significantly as better practices and resources spread.…”
Section: Koindu To Darumentioning
confidence: 99%
“…Rolled out to correspond with the ruling party's re‐election campaigns in 2012, the programme was rushed and disorganised, plagued by inefficiency and graft (Pieterse and Lodge 2015). Newly hired medical workers and informal volunteer nurses found themselves forced to “make‐do” with poorly regulated, improvisational methods of diagnosis and treatment (Park 2017). Nonetheless, the programme attracted funding to fast‐track training for village‐level health posts.…”
Section: Koindu To Darumentioning
confidence: 99%